Determinants of Fraud Prevention with Professional Ethics as a Moderator - Agus Proklamasi Simatupang; Syahril Djaddang; Endang Etty Merawati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Fraud remains a critical challenge for plantation and agribusiness companies due to the complexity of operational processes, extensive resource management, and increasing digitalization. This study aims to examine the determinants of fraud prevention by analyzing the influence of information systems, internal audit, audit competence, and whistleblowing systems, while also investigating the moderating role of professional ethics. A quantitative research approach was employed using survey data collected from 100 practitioners working in plantation and agribusiness companies. The data were analyzed using Moderated Regression Analysis (MRA) to assess both direct and moderating effects among the variables. The findings reveal that information systems and audit competence have significant positive effects on fraud prevention, indicating that technological support and auditor expertise play important roles in strengthening organizational control mechanisms. In contrast, internal audit and whistleblowing systems do not demonstrate significant effects on fraud prevention. The results further show that professional ethics significantly moderates the relationship between audit competence and fraud prevention by strengthening the effectiveness of competent auditors in detecting and preventing fraudulent activities. However, professional ethics does not significantly moderate the relationships between information systems, internal audit, whistleblowing systems, and fraud prevention. These findings suggest that effective fraud prevention in plantation and agribusiness companies requires not only robust information systems and competent auditors but also strong ethical values that enhance professional judgment and accountability. The study contributes to the fraud prevention literature by highlighting the strategic role of professional ethics in reinforcing the impact of audit competence on organizational fraud prevention efforts. The results provide practical implications for managers, auditors, and policymakers seeking to improve governance and fraud control practices within the plantation and agribusiness sector.